KARAKTERISTIK KIMIAWI FLY ASH BATU BARA DAN POTENSI PEMANFAATANNYA SEBAGAI BAHAN PUPUK ORGANIK - Sari Widya Utami (Agroindustrial Technology, University of Trunojoyo Madura, 2018)
The purpose of the research was to study the content of chemistry of fly ash and the its potention of fly ash as the matterial of organic fertilizer. The research was conducted by mixing fly ash with some organic matterials with comparison 1:9. The element content of organic fertilizer was compared to the quality standard of organic fertilizer based on Government Regulation. The result of the research showed that the adding of fly ash could increase the value of pH and it did not increase some macro nutrients and the heavy metal content.